Associations between RAD51D germline mutations and breast cancer risk and survival in BRCA1/2-negative breast cancers. (27th August 2018) - Chen, X; Li, Y; Ouyang, T; Li, J; Wang, T; Fan, Z; Fan, T; Lin, B; Xie, Y
Abstract: Background: RAD51D is involved in DNA double-strand break repair by homologous recombination and plays an important role in the maintenance of genomic stability. The associations between RAD51D germline mutations and breast cancer risk and survival are not fully elucidated. Patients and methods: RAD51D germline mutations were determined using a multigene panel in 7657 unselected breast cancer patients who were negative for BRCA1/2 germline mutations. The RAD51D recurrent mutation p.K91fs was screened in 7947 healthy controls by Sanger sequencing. Results: A total of 29 cases (0.38%) carried deleterious RAD51D germline mutations among this cohort of 7657 unselected breast cancer patients. The RAD51D recurrent mutation p.K91fs was identified in 18 cases (0.24%) of these 7657 patients. In contrast, the p.K91fs mutation was found in 8 of 7947 healthy controls with a frequency of 0.10%. The RAD51D p.K91fs mutation was significantly associated with increased breast cancer risk in unselected breast cancer [odds ratio = 2.34, 95% confidence interval (CI) 1.02–5.38; P = 0.040]. RAD51D mutation carriers were diagnosed at a younger age ( P = 0.006) and were more likely to be triple-negative breast cancer ( P = 0.003), estrogen receptor negative ( P = 0.005) and high-grade cancers ( P = 0.023) than noncarriers. Furthermore, RAD51D mutation carriers had a significantly worse recurrence-free survival [unadjusted hazard ratio (HR) = 3.00, 95% CI 1.56–5.80; P = 0.001] and distant recurrence-free survival (unadjusted HR = 2.54, 95% CI 1.14–5.67; P = 0.023) than noncarriers. Conclusion: The RAD51D recurrent mutation, p.K91fs, confers a moderately increased breast cancer risk, and RAD51D mutation carriers have an unfavorable survival compared with noncarriers.